New insight into the mechanism of POP-induced obesity: Evidence from DDE-altered microbiota. (April 2020) - Liang, Yiran; Liu, Donghui; Zhan, Jing; Luo, Mai; Han, Jiajun; Wang, Peng; Zhou, Zhiqiang
Abstract: Although epidemiological studies demonstrate that persistent organic pollutants (POPs) could lead to metabolic syndrome, the mechanism has remained unclear. The dysbiosis of gut microbiota and the lipid metabolome have been put forward in the pathophysiology of metabolic syndrome. In this study, we used dichlorodiphenyldichloroethylene (DDE) as an example to study the effects of POP-impaired microbial composition and metabolome homeostasis on metabolic syndrome. The results showed that DDE exposure increased body weight and fat content and impaired glucose homeostasis. Further investigation revealed that DDE induced gut dysbiosis as indicated by an increased Firmicutes -to- Bacteroidetes ratio, which may impact energy harvest efficiency. Meanwhile, the plasma lipid metabolome profile was significantly altered by DDE. Furthermore, phosphatidylcholine, phosphatidylserine, phosphatidylethanolamine, and triacylglycerol were identified as key metabolites affected by DDE treatment, and these altered lipid metabolites were highly correlated with changed microbiota composition. This study provides novel insight into the underlying mechanism of POP-induced obesity and diabetes, pointing to gut microbiota as one of the targets. Highlights: DDE exposure led to increased fat content and impaired glucose homeostasis. DDE exposure induced obesity-related microbiota composition shift. DDE exposure induced obesity-related plasma metabolome shift.